IMPLEMENTASI COMPUTERIZED RESERVATION SYSTEM (CRS) PADA MASKAPAI FIREFLY RUTE PEKANBARU – SUBANG - Nia Chetiajar Dalimunthe; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of conduching this research is to know how the efficiency aystem and menu of firefly enterprise on Pekanbaru – Subang rute.This research used descriptive methode to analyze the probloms. The sample of this research was 57 travel agent which was taken by accidental sampling. The technique of collecting data in this research used observation, questionaire and interview. To know the interval range, the writer used likert scale.Based on the result of this research. The respon of the respondence about the implementation of computerized reservation system (CRS) on the firefly enterprise with theree sub variables. The three sub variables are providing price information and kinds reservation of facility services, tickeet publishing, administration (back office accounting support) band office automation, the respon is anough.Key words : Implementation, Computerized Reservation System (CRS), Firefly Enterprise